2016
DOI: 10.1016/j.rboe.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effect of beta-tricalcium phosphate with zeta potential control in repairing critical defects in rats’ calvaria

Abstract: ObjectiveTo evaluate whether a new biphasic cement composed of calcium sulfate and beta tricalcium phosphate with zeta potential control could induce or lead to bone neoformation in critical defects.MethodsA critical defect of diameter 8 mm was made in the calvaria of forty male Wistar rats. In the Test Group (n = 20), the defects were filled with cement. In the Control Group (n = 20), the defect was not filled and only coagulum was present. The animals were sacrificed 7, 14, 21 and 42 days after the operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The similarity in stain intensity and morphology of both H&E and Masson’s trichrome staining further confirmed the different regeneration potential of the hybrid scaffold in the absence and presence of rBMSCs. In Masson’s trichrome staining, the deep blue-colored array of longitudinal stain in the sections of the cellular scaffold disclosed the osteoid formation (red arrows), while the cluster of cells denoted by black arrows endorsed the existence of osteoblasts [59,60]. When rBMSCs differentiate into osteoblasts, osteoids (organic portion of the bone matrix) will be embedded in the newly formed tissue matrix, and thus, could be proved through staining for connective tissues.…”
Section: Resultsmentioning
confidence: 99%
“…The similarity in stain intensity and morphology of both H&E and Masson’s trichrome staining further confirmed the different regeneration potential of the hybrid scaffold in the absence and presence of rBMSCs. In Masson’s trichrome staining, the deep blue-colored array of longitudinal stain in the sections of the cellular scaffold disclosed the osteoid formation (red arrows), while the cluster of cells denoted by black arrows endorsed the existence of osteoblasts [59,60]. When rBMSCs differentiate into osteoblasts, osteoids (organic portion of the bone matrix) will be embedded in the newly formed tissue matrix, and thus, could be proved through staining for connective tissues.…”
Section: Resultsmentioning
confidence: 99%
“…It supports the orbital structures, and separates the oral and orbital cavities [ 9 ]. Autogenous bone graft is considered the material of choice for the reconstruction of bone in maxillofacial surgery [ 1 ]. However, to prevent secondary donor site morbidity and increased duration of the operation for the harvesting procedures, several artificial bone substitutes, including bioceramics, allograft bone matrix, and composites have been developed for craniofacial defects [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Foreign body reaction is a response of wound healing following the insertion of biomaterials and it may play a major role in the formation of bony spicules, calcified clusters, and sinuses [ 1 10 11 ]. de Souza et al reported foreign body reaction and inflammatory infiltrates in β-TCP insertion sites; they hypothesized that it may lead to expulsion of β-TCP clusters from the original defect site [ 1 ]. Sinus formation resulting from foreign body reaction was also reported [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations